Is rewilding too wild? Assessing the benefits and challenges of forest succession on abandoned land in the mid‐hills of Nepal - Nicola McGunnigle; Douglas Bardsley; Ian Nuberg; Bishnu Hari Pandit (People and Nature)
Abstract The rewilding of landscapes through the promotion of natural ecological processes is a contemporary approach to nature restoration and conservation. In Nepal and elsewhere globally, forest is also regenerating naturally on abandoned agricultural land, effectively rewilding the landscape by default. We investigate factors that lead to reforestation and examine tensions and trade‐offs in rural areas traditionally dependent on agriculture for subsistence livelihoods. Perceptions of forest succession in the middle hills of Nepal are analysed in relation to views of rewilding. We examine rural households' experiences of naturally regenerating forest and compare those insights with perceptions of the concept of rewilding as understood by environmental management professionals in Nepal. We assess the perceived benefits of regenerating species and the challenges to acquiring these benefits for forest‐based livelihoods. The causes of agrarian‐forest transitions are complex and often compounding. With out‐migration from rural areas and a shift away from subsistence agriculture, new and cyclic conflicts are emerging. Although the processes of rewilding and regenerating forest are largely synonymous, language such as ‘wild’ and ‘wilderness’ is associated with negative experiences of human–wildlife conflict and invasive species, suggesting the term ‘rewilding’ poses more challenges with regard to forest transitions than ‘regenerating forest’. However, research participants identified beneficial livelihood and conservation opportunities from regenerating forest species and emphasised the potential for co‐existence of emerging forests within traditional agricultural landscapes. The epistemology is therefore vital for framing conceptions of forest transitions. Guiding stakeholders to identify and develop opportunities for regenerating forests during transitions is possible. Diverse livelihood benefits were recognised by rural households in the study area, with some respondents adopting agroforestry systems using regenerating species. Policy implications: Policy development around land use change needs to realise that multiple issues lead to and arise from agrarian‐forest transitions. Regenerating forests could contribute to global biodiversity targets through development pathways promoting the emerging biota that also contribute to livelihood benefits. Steps to work with, rather than against, the causes and effects of natural regeneration could deliver positive outcomes for sustainable livelihoods and biodiversity conservation in Nepal and beyond. Read the free Plain Language Summary for this article on the Journal blog.